An in vitro comparison of microleakage of two self-etched adhesive and the one-bottle adhesive used in pit and fissure sealant with or without saliva contamination - Leila Bassir; Mashaallah Khanehmasjedi; Ehsan Nasr; Azita Kaviani (Wolters Kluwer Medknow Publications, 2012)
Aims and Objectives: To minimize the deleterious effects of contaminated enamel on bonding, some authors have advocated the use of adhesive systems under the sealant. The aim of this study was to compare the microleakage of two self-etch and the one-bottle adhesive used in pit and fissure sealant with or without saliva contamination. Materials and Methods: Sixty extracted premolar teeth were assigned to the six groups. Group 1: Acid +saliva +single bond +sealant, Group 2: Acid +single bond +sealant, Group 3: Saliva +S 3 bond +sealant, Group 4: S 3 bond +sealant, Group 5: Saliva +protect bond +sealant, Group 6: Protect bond +sealant. The teeth were thermocycled and immersed in 2% basic fuchsine dye for 24 h, then sectioned and examined with a stereomicroscope under ×40 magnification. The results were evaluated with Kruskal-Wallis and Dunn tests. Results: Group 2 has the lower microleakage scores than Groups 4 and 6. Also, Group 6 has the lower microleakage scores than Group 4, and generally an increase in microleakage was observed in each group related to contamination. Conclusion: The best technique of sealant therapy in saliva contaminated and non- contaminated condition is the use of acid-etching and bonding agent.